A scoping review of the effects of classroom acoustic conditions on primary school children's mental wellbeing. Issue 4 (December 2022) - Mealings, Kiri
The aim of this scoping review was to systematically map research on the effect of classroom acoustic conditions on children's mental wellbeing and identify existing gaps in knowledge to inform future research. This scoping review followed the PRISMA-ScR protocol. A comprehensive search of four online databases (ERIC, PubMed, Scopus, and Web of Science) was conducted using the search term classroom AND (acoustic* OR noise OR reverb*) AND ("mental health" OR emotion OR wellbeing OR "quality of life" OR anxiety OR depression). Peer-reviewed papers were included if they were written in English, included children in the primary school age range (i.e. 5–12 years), and included a measure of children's mental wellbeing. Six papers met the criteria to be included in the review. Overall, this review suggests that poor classroom acoustic conditions can negatively affect children's mental wellbeing. Given the small number of studies, future research suggestions are proposed to fill current gaps in knowledge.